Ad-Apoptin-hTERTp-E1a Regulates Autophagy Through the AMPK-mTOR-eIF4F Signaling Axis to Reduce Drug Resistance of MCF-7/ADR Cells - Li, Yaru; Zhu, Yilong; Han, Jicheng; Fang, Jinbo; Xiu, Zhiru; Li, Shanzhi; Li, Wenjie; Yang, Xia; Jin, Ningyi; Sun, Lili; Li, Xiao; Li, Yiquan (Frontiers in Molecular Biosciences, 2021)
Ad-VT (Ad-Apoptin-hTERTp-E1a) is a type of oncolytic adenovirus with dual specific tumor cell death ability. It can effectively induce cell death of breast cancer cells and has better effect when used in combination with chemotherapy drugs. However, it has not been reported whether Ad-VT reduces the resistance of breast cancer cells to chemotherapy drugs. The purpose of this study is to investigate the effect of Ad-VT on drug resistance of Adriamycin-resistant breast cancer cells. For this, the effects of different doses of Ad-VT on the resistance of breast cancer cells to Adriamycin were analyzed using qualitative and quantitative experiments in vitro and in vivo. The Ad-VT can reduce the resistance of MCF-7/ADR to adriamycin, which is caused by the reduction of MRP1 protein level in MCF-7/ADR cells after treatment with Ad-VT, and MRP1 can be interfered with by autophagy inhibitors. Subsequently, the upstream signal of autophagy was analyzed and it was found that Ad-VT reduced the resistance of cells to doxorubicin by reducing the level of mTOR, and then the analysis of the upstream and downstream proteins of mTOR found that Ad-VT increased the sensitivity of MCF-7/ADR cells to adriamycin by activating AMPK-mTOR-eIF4F signaling axis. Ad-VT can not only significantly induce cell death in MCF-7/ADR cells, but also improved their sensitivity to Adriamycin. Therefore, the combination of Ad-VT and chemotherapy drugs may become a new strategy for the treatment of breast cancer in overcoming Adriamycin resistance.